1969
DOI: 10.1136/gut.10.9.735
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse hypertrophy of gastric mucosa (Menetrier's disease) and iron-deficiency anaemia

Abstract: SUMMARY A 23-year-old woman presented with intractable iron-deficiency anaemia. A barium meal showed widespread mucosal abnormalities in the stomach and massive mucosal hypertrophy was found at laparotomy. Repeated tests for occult blood were negative but gastrointestinal haemorrhage was confirmed by isotopic blood labelling. In the face of persistent anaemia and radiological progression, total gastrectomy was performed, since when a normal blood picture has been maintained. The excised stomach showed hyperpla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1971
1971
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…In addition, previous cases of MD have also presented with severe iron-deficiency anemia (14,15). In the present case, anemia and hypoproteinemia were successfully eliminated by red cell transfusion and intravenous iron therapies.…”
Section: Discussionmentioning
confidence: 53%
“…In addition, previous cases of MD have also presented with severe iron-deficiency anemia (14,15). In the present case, anemia and hypoproteinemia were successfully eliminated by red cell transfusion and intravenous iron therapies.…”
Section: Discussionmentioning
confidence: 53%
“…5 It may, therefore, be concluded that the thrombocytosis detected in the case presented is far from being a mystery and is merely the result of the interplay of two factors, namely, chronic rectal bleeding and oral iron therapy. After the initiation of therapy, platelets start to rise on the third or fourth day, reaching some¬ times higher than normal levels or, at least, attain the upper limit of nor¬ mal, and return sometime within a month to completely normal quan¬ tities even in patients with hypersplenism.…”
mentioning
confidence: 79%
“…It has been said to be due to prolapsing of the mucosa through the pylorus. In 4 previously reported cases, severe haematemesis was the indication for emergency surgery (Dickinson and Axon, 1979;Singh et al, 1979). Occult bleeding is more common and, in T.S.…”
Section: Discussionmentioning
confidence: 99%
“…The condition was first described by Menetrier in 1888 and since then some 200 cases have been reported in the literature. These reports have concerned the pathology (Butz, 1960), the protein turnover (Jarnum and Jensen, 1972;Jones et al, 1972), the gastric protein loss (Citrin, Sterling and Halstead, 1957) and case reports of the various types of presentation, notably acute gastrointestinal (GI) bleeding (Williams, 1956), chronic GI bleeding (Singh, Cumaraswamy and Corrin, 1979), and oedema (Chokas, Connor and Innis, 1959). Diarrhoea has occasionally been reported.…”
Section: Introductionmentioning
confidence: 99%